SOIL PROPERTIES OF THE ALLUVIAL PLAIN AND ITS POTENTIAL USE FOR AGRICULTURE IN DONGGALA REGION, CENTRAL SULAWESI - Al-Jabri, M. (Indonesian Agency for Agricultural Research and Development - MOA, 2007)
Agricultural lands of Donggala region are extensively distributedin alluvial plain. However, information on soil properties andfertility constraints has not been known in detail. An investigationof soil resources was conducted in September 2003 andDecember 2004 to characterize surface soil properties of alluvialplain and to evaluate soil fertility constraints. For this study,55 representative soil profiles consisting of 187 soil sampleswere selected for physical, chemical, and mineralogical analyses.The soil profiles were classified as soil groups of Ustifluvents,Haplustepts, Eutrudepts, and Endoaquepts. All the soil physicaland chemical data were calculated as weighted average based ontop 30 cm soil layer analyses. The results showed that soil textureranged from sandy loam to loam. In ustic moisture regime,the average pH was neutral (7.0-7.2), but in udic moisture regimeit was slightly acid (5.5-6.2). In all soil groups, the organiccarbon content was very low to low (0.58-1.44%), P retentionwas very low (3-18%), and soil cation exchange capacity (CEC)was very low to low (9-14 cmol(+) kg-1). In contrast, all the soilgroups showed very high content of potential phosphate (81-118 mg P2O5 100 g-1) and potassium (338-475 mg K2O 100 g-1),but the available phosphate and potassium were 16-47 mg kg-1P and 0.18-0.35 cmol(+) kg-1, respectively, which were consideredto be low to medium range. The very high P2O5 and K2O wereprobably derived from weathered mica-schist and granite rocks,but low exchangeable K was probably due to K fixation. Thesand mineral fraction was composed of relatively high (> 20%)weatherable minerals of acid parent materials, such as orthoclaseand sanidine, while the clay mineral was composed ofsmectite and illite. The low soil-CEC, low organic matter, andexchangeable K contents were the main soil fertility constraints.Therefore, soil management should be directed to organic matterapplication to increase soil carbon content, CEC, and nutrientavailability. Fertilizer recommendation for wetland rice and severalupland crops is suggested based on the soil properties.